Propuesta para el diseño de documentación del SG-SST bajo la Resolución 0312 del 2019 para la empresa Maderera La Isla Ciudad Acacias Meta - Carmen Piñeros Villa, Helen Barrera Castillo (Universidad Antonio Nariño, 2021)
This Degree Project is based on the development of a proposal for the documentation of the Occupational Health and Safety Management system for the La Isla Timber company in the City of Acacias Meta, under Resolution 0312 of 2019 which determines the Minimum SG-SST standards, which must be adjusted to each company according to need, where the economic activity, number of workers, and the work carried out must be taken into account. The development of the SG-SST ensures the protection and general well-being of the human talent that works in the company and also contributes to social responsibility, but also to the current regulations issued by the Ministry of Labor of Colombia.